Surgical Reconstruction of Old and Neglected Tendo Calcaneus Injury: Experience of 20 Cases in Bangladesh - Islam, Md Nazrul; Islam, Md Rabiul; Begum, Tahmina; Islam, Md Moshabbirul; Syeed-Ul-Alam, SM (Journal of Current and Advance Medical Research, 2023)
Background: Treatment of old and neglected rupture of Tendo calcaneus is difficult due to formation of wide gap between the two ends. Objective: This present study was aimed to assess the post-operative outcomes of surgical reconstruction of old and neglected Tendo calcaneus injury. Methodology: This was a non-randomized clinical trial which was conducted at Department of Orthopedic Surgery, Ad-Din Sokina Women’s Medical College, Jashore, Bangladesh from January 2017 to December 2020 for a period of 4 years. The patients aged between 18 to 60 years were selected for this study after fulfilling the inclusion and exclusion criteria. Results: All patients were non diabetic and normotensive. Affected Tendons were on both sides. Out of 20 patients 16 male and 04 were female. Twenty patient from 18 to 60 year were included in this study and obtained excellent result with this reconstruction surgery. Success rate was considered almost 100 present. Only one patent developed mild wound infection. Conclusion: Old neglected rupture of Tendo calcaneus is very difficult problem as patients become unable to walk properly. Journal of Current and Advance Medical Research, January 2023;10(1):3-6